What Divides the First and Second Generations? Family Time of Arrival and Educational Outcomes for Immigrant Youth - Marie C. Hull (Institute of Labor Economics (IZA), 2022)
In this paper, I develop a measure of host country experience, which I call "relative time of arrival," to explore differences between first- and second-generation immigrants. This measure is finer than immigrant generation and expands on the widely used measures of years since migration and age at migration. It is scaled so that zero indicates that a child was born in the same year that the family migrated. I then use this measure to study the dividing line between the first and second generations, specifically, whether there are differences in educational outcomes between early-arriving first-generation immigrants and second-generation immigrants whose parents arrived shortly before birth. For most outcomes considered, I find that the transition between the first and second generations is relatively smooth, indicating that these groups are not as distinct as often thought. I also use the measure assess whether parents' host country experience before a child's birth matters and generally find that it does not. Consistent with prior work, I show that outcomes measuring English knowledge are negatively related to age at arrival. Thus, observed differences between the first and second generations are driven by the lower performance of late-arriving first-generation children.
Keywords: I24; J13; J15; 330; children of immigrants; immigrant generation; age at arrival; educational attainment; achievement; parental inputs